Bacterial microbiota of the upper respiratory tract and childhood asthma - Depner,M; Ege,MJ; Cox,MJ; Dwyer,S; Walker,AW; Birzele,LT; Genuneit,J; Horak,E; Braun-Fahrländer,C; Danielewicz,H; Maier,RM; Moffatt,MF; et al. (Journal of Allergy and Clinical Immunology, 2016)
BACKGROUND: Patients with asthma and healthy controls differ in bacterial colonization of the respiratory tract. The upper airways have been shown to reflect colonization of the lower airways, the actual site of inflammation in asthma, which is hardly accessible in population studies. OBJECTIVE: We sought to characterize the bacterial communities at 2 sites of the upper respiratory tract obtained from children from a rural area and to relate these to asthma. METHODS: The microbiota of 327 throat and 68 nasal samples from school-age farm and nonfarm children were analyzed by 454-pyrosequencing of the bacterial 16S ribosomal RNA gene. RESULTS: Alterations in nasal microbiota but not of throat microbiota were associated with asthma. Children with asthma had lower α- and β-diversity of the nasal microbiota as compared with healthy control children. Furthermore, asthma presence was positively associated with a specific operational taxonomic unit from the genus Moraxella in children not exposed to farming, whereas in farm children Moraxella colonization was unrelated to asthma. In nonfarm children, Moraxella colonization explained the association between bacterial diversity and asthma to a large extent. CONCLUSIONS: Asthma was mainly associated with an altered nasal microbiota characterized by lower diversity and Moraxella abundance. Children living on farms might not be susceptible to the disadvantageous effect of Moraxella. Prospective studies may clarify whether Moraxella outgrowth is a cause or a consequence of loss in diversity.